Review on video privacy protection - Ling-ling TONG; Yang-xi LI; Wen-ting HUANG (Tongxin xuebao)
With the rapid development of the Internet and the tremendous proliferation of video applications,video privacy protection has garnered significant attention nowadays.It is a key problem to protect privacy while ensuring normal application.A survey of video privacy protection technologies was presented,and summary,comparison and analysis were mainly in three aspects:privacy extraction,privacy protection and access control.Moreover,some distinctive issues that correlate to privacy protection in video surveillance,such as privacy definition and perceptive security evaluation were also addressed.Finally,challenges and perspectives of video privacy protection technology were discussed.